Formulação de um indicador de acessibilidade das calçadas e travessias - Keppe Junior, Celso Luiz Guimarães (Universidade Federal de São Carlos, 2007)
The present dissertation work in Urban Engineering of the Federal University of São Carlos (UFSCar) aims to define an easy and practical form of evaluating the level of service in public spaces destined to the carriers of physical deficiency (sidewalks and streets passages) through the determination of an index that considers the parameters of higher importance by the point of view of wheelchair users. The index is defined through the identification and the ordinance of variables based on physical and environment characterization of sidewalks related to aspects of quality such as comfort, security and conditions of the environment. The weighing scale of the variables of physical and environment characterization of sidewalks (importance degree) is carried through analysis based on wheelchair users perception, therefore defining the ISPA - Index of Sidewalks and Passages Accessibility, and verifying its functionality through auditor work also performed with wheelchairs users advice in two places of São Carlos city. Through this tool of evaluation, the agencies of road management can evaluate the quality of the public spaces in a total route or specific stretches of the essential displacements for the real participation of the person with locomotion difficulties in society.
Keywords: Acessibilidade; Cadeira de rodas; Qualidade nas calçadas; Wheelchair; Accessibility; Indicators; Quality; Auditor work; Sidewalk; Passages; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO::PLANEJAMENTO E PROJETO DO ESPACO URBANO